Antibiotics Sensitivity Profile Towards Staphylococcus hominis in Assir Region of Saudi Arabia (Journal of Scientific Research, 2012)
Staphylococcus hominis is a Gram-positive, spherical cells in clusters and coagulase-negative bacterial. It commonly occurs as a harmless commensal on human skin, occasionally causes nosocomial or community acquired infection specially in immuno-compromised patients. Nowadays almost all Staphylococcus species have multidrug resistance. In this study, a total of ten out of one hundred fifty nasal swabs at Assir Central Hospital General Lab during the period of April 2011- July 2011 proved to be Staphylococcus spp. and identified as  Staphylococcus hominis  patients of different sex and age groups with variable systemic infections (e.g. RTI, UTI, CNS).  The samples were tested by bactech, culture media, antibiotics sensitivity using diffusion disc test (MIC) and molecular polymerase chain reaction (PCR) for confirmation of Staphylococcal species and detection of the Mec A gene. Clinical, demographic and laboratory data were collected and analyzed by SPSS. Drugs found to be resistant to all patients were penicillin, erythromycin, ampicillin, cifoxine and carbinicillin. Whereas cotrimexazole, amikacine and vancomycine were sensitive to all patients. Only 10% of patients were sensitive to methotrexate and cefaclor. Drugs that showed variable sensitivity pattern among patients were tetracyclin, fucidin, augmentin, gentamycin and ciprofloxacin.© 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved.doi: http://dx.doi.org/10.3329/jsr.v5i1.11704        J. Sci. Res. 5 (1), 171-183 (2013)